Principal Response Curves analysis of polyphenol variation in resistant and susceptible cotton after infection by a root-knot nematode (RKN) - Alves, Gleina C.S.; Ferri, Pedro H.; Seraphin, José C.; Fortes, Gilmara A.C.; Rocha, Mara R.; Santos, Suzana C. (Physiological and molecular plant pathology, 2016)
The root-knot nematode (RKN), Meloidogyne incognita, attacks cotton root system. This study aimed to compare the induction of phenolic compounds over time in two cotton genotypes, resistant (TX-25) and susceptible (FM966), by RKN. Chemical profiles of cotton roots were obtained by HPLC, NMR, and colorimetric methods at four different time intervals. The Principal Response Curves analysis, a time-dependent, multivariate method, showed consistent variability over time in the profile of phenolic compounds between treatments for both genotypes. The variables that most contributed to the divergence between damaged and undamaged cotton roots were dimethoxylated and non-methoxylated gossypols, total flavonoids, and total phenols. •PRC analysis showed variability over time in the chemical profile of Gossypium hirsutum.•The nematode influences the chemical pattern of both G. hirsutum genotypes.•Phenolics contributed to the divergence between damaged and undamaged G. hirsutum.•Gossypols, flavonoids, and total phenols were the main compounds induced by RKN.